A semantic study of anxiety in Arabic literature and its psychotherapy in the works of selected early Muslim scholars - Abdul Latif Abdul Razak (International of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2005)
Anxiety, which is a general state of apprehension and worry, is one of the most prevalent mental disorders suffered by human beings. It is often associated with in ability to cope with true or imaginary hardships. Anxiety-ridden people are really in need of an effective remedy that truly cures. Nowadays, the most dominant theories of anxiety, its diagnosis and treatments, which influence people all over the world including the Muslims, stem from Western secular minded psychologists. Since their secular and materialistic views of man as an animal are neither comprehensive nor really helpful because they reject the spiritual aspects of man, their theories could not serve as a proper solution to the problems of anxiety particularly with Muslim patients. Islamic psychology, on the other hand, looks at man in a comprehensive manner that takes into consideration his spiritual and physical aspects. This provides a better understanding of anxiety and its treatments: It could help to solve this problem truly and not superficially as in the case of Western psychology. Unfortunately, such contents of psychology remain in the close folds of the writings of early Muslim scholars such as Riyadah wa Adab al-Nafs by al-Tirmidhi, Ihya' 'Ulum al-Din by al-Ghazfili, Al-Ri'ayat li Huquq Allah by al-Mul;lasibi, Tahzib al-Akhlaq wa Tath'ir al-A 'raq by Ibn Miskawayh, Tibb al-Ruhani by al-Razi, Masalih al-Abdan wa al-Anfus by Abu Zayd al-Balkhi, and Al-Ruh by Ibn Qayyim .. Thus, the aim.of my dissertation,is to bring.forward and,highlight this useful heritage with the hope that it will serve the need of people especially the Muslims.